2020
DOI: 10.1038/s41467-020-14824-w
|View full text |Cite|
|
Sign up to set email alerts
|

Response outcomes gate the impact of expectations on perceptual decisions

Abstract: Perceptual decisions are based on sensory information but can also be influenced by expectations built from recent experiences. Can the impact of expectations be flexibly modulated based on the outcome of previous decisions? Here, rats perform an auditory task where the probability to repeat the previous stimulus category is varied in trial-blocks. All rats capitalize on these sequence correlations by exploiting a transition bias: a tendency to repeat or alternate their previous response using an internal esti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(132 citation statements)
references
References 45 publications
5
115
0
Order By: Relevance
“…Fig. 1) (Hermoso-Mendizabal et al 2020). Importantly, as with the reset strategy, this disregard of any information involving error trials is not optimal, since in the 2AFC task all types of transitions are equally informative (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1) (Hermoso-Mendizabal et al 2020). Importantly, as with the reset strategy, this disregard of any information involving error trials is not optimal, since in the 2AFC task all types of transitions are equally informative (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation (possibly temporally discounted) of action outcomes also underlies several reinforcement learning algorithms ( 4, 2729 ). Although less attention has been devoted to reset-like computations (but see ( 30 )), they are also essential for inference when certain observations specify a state unambiguously ( 2 ). Our results show that these computations can be cast into a single parametric generative model capable of producing a set of decision variables embodying a variety of stimulus-bound and inference-based strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A source for choice biases and their dependence on recent history could involve stable working memory representations ( Fischer and Whitney, 2014 ; Fritsche et al, 2017 ; Urai et al, 2019 ). History effects on choice have been observed in humans ( Fischer and Whitney, 2014 ; Abrahamyan et al, 2016 ) and rodents ( Busse et al, 2011 ; Akrami et al, 2018 ) and are present in forced-choice ( Gold et al, 2008 ; Fischer and Whitney, 2014 ), memory-guided ( Akrami et al, 2018 ; Hermoso-Mendizabal et al, 2018 ), and free-choice tasks ( Sugrue et al, 2004 ; Lau and Glimcher, 2005 ). We also found that mice and humans adapted their behavioral strategies depending on the discriminability trajectories established during training ( Ahissar et al, 2009 ; Trevino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%